Jean CHESNEAUX, Marianne BASTIDE, Marie Claire BERGÉRE, China from the Opium Wars to the 1911 Revolution, New York, Pantheon Books, 413 pp. - Pinheiro Juárez Coqueiro (El Colegio de México, A.C., 1980)
-